KORELASI ANTARA KEDISIPLINAN DAN PRESTASI BELAJAR PESERTA DIDIK DI MI NURUL AMAL (KECAMATAN GEDUNG MENENG KABUPATEN TULANG BAWANG) - MAHMUDI, MAHMUDI; AMRIYAH, CHAIRUL (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
Education is a process of self-development and personality formation. Discipline is an attitude that a student should have because it is a part of formation of personality. Discipline in the school environment is needed to create a comfotable learning athmosphere for teachers and students. Tha application of discipline is expected to assist the students to reach optimal achievement. Thus. the objection of this research is to find out whether there is a possitive correlation between discipline and students’ learning achievement. This was a quantitative reasearch. It was conducted in MI Nurul Amal. Gedung Meneng. Tulang Bawang. There were 34 students of fifth grade as the population. Data of the research was gained by using questionnaire as the primary technique. Observation was used as the supporting technique. Documentation technique was also used to know teacher’s preparation in conducting teaching-learning process. Based on data analisys. the result was robserved  > rtable. This result proved that there was a possitive correleation between between discipline and students’ learning achievement. It meant that the better students have discipline. the higher achievement they can reach.